(untitled) (Research, Society and Development, 2021)
The Altamira creek, one of the three components of the Xingu River sub-basin, in western Pará, was subject to intense degradation due to irregular occupation on both banks of the urban area of this municipality. North Energy S/A, relocated the population and started the environmental recovery of this water body, with the intention of transforming the site into a Conservation Unit after the recovery is completed. The objective of this research was to evaluate qualitatively and quantitatively, the impacts on the environment and communities before and after the intervention of the company responsible for the Belo Monte HPP, the positive and negative changes of these transformations and to compare the two scenarios. The method used was observational, systematic, direct, in situ, photographic memorial construction, and the making of two Leopold Matrices adapted for their identification and evaluation. The data obtained and analyzed indicated that (1) environmental recovery was characterized as positive; (2) negative impacts still occur at the site, which have been mitigated. We conclude that the initial situation was mitigated, but the negative impacts still occurring must be resolved with the completion of the work and achieve the goal set by the company.